Menumbuhkan Sinergitas Pengawas dengan Tenaga Pendidik di Madrasah Binaan - Dodo, Dodo (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
This study aims to illustrate the role of supervision of madrasah supervisors in understanding the competence of supervisors in an effort to improve the quality of education. This research uses a descriptive method with a qualitative approach and was conducted in 12 assisted madrasahs in Lakbok District until June 2022. Data were collected through interviews, observations, and documentation studies. The results showed that the paradigm of teachers towards supervisors was initially negative, but experienced positive changes after interventions in the form of more collaborative approaches, guidance, and better communication. These results demonstrate the importance of effective communication between teachers and supervisors in creating synergies that support the learning process.